Identifikasi Cacing Endoparasit Pada Saluran Pencernaan Ikan Tongkol (Euthynnus Affinis) Dari Pasar Tradisional Di Kabupaten Sampang Madura - Lailatul Maghfiroh, - (2021)
This study aims to identify, determine the persentase rate and infection of endoparasite helminth in Tongkol (Euthynnus affinis) from the Traditional Market in Sampang District, Madura. The samples were used in research this in the 60 tail fish cobs were purchased from seven Markets Tradisional in Sampang regency. Samples in the surgery done Staining helminth using the methods Semichen-Acetic Carmine. Do it microscopically with a magnification of 100x and 400x to know the helminth endoparasite. Results show from 60 fish cob 56 fish infected by Anisakis sp and Terranova sp.